Utility-consistent poverty in Ethiopia, 2000 - 11: Welfare improvements in a changing economic landscape - David Stifel; Tassew Woldehanna (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
We use Arndt and Simler's utility-consistent approach to calculating poverty lines to analyse poverty in Ethiopia in 2000, 2005, and 2011. Poverty reduction was steady but uneven, with gains greatest in urban areas in the first half of the decade, and in rural areas in the latter half. Other monetary and non-monetary measures of well-being confirm the general pattern of persistent improvements, though the large declines in poverty are not entirely supported by the magnitudes of change in other measures. Nonetheless, data comparability issues warrant that great care be taken in interpreting the degree to which poverty fell.
Keywords: D63; I32; O55; 330; poverty measurement; utility-consistent poverty lines; inequality; Ethiopia